DIFFERENCES IN STUDENT LEARNING OUTCOMES: CASE BASED LEARNING METHODS (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2023)
This study wants to test whether there are differences in learning outcomes for college students of different cultures and generations. They are students of Universitas Pendidikan Indonesia (UPI), Universitas Negeri Malang (UM), and Universitas Siliwangi Tasikmalaya (UNSIL). With a population of 105 people, the sample used is a saturated sample. The research method used is nonparametric. The results showed that there were no differences in learning outcomes between UPI, UM and UNSIL students in the economics education course using the case based learning method in the digital learning innovation program (MBKM).